STUDI DESKRIPTIF KETIDAKLENGKAPAN DOKUMEN REKAM MEDIS RAWAT INAP PADA KASUS DEMAM - Sayati Mandia (Iris Journal of Health Information Management, 2021)
Dengue fever has become a global public health problem. Epidemiological measurements of the DHF burden such as incidence and prevalence are important for policy making and monitoring progress in disease control. The WHO reports that the global incidence of dengue has increased 30-fold in the past 50 years and it is estimated that between 50 and 100 million new infections occur each year, resulting in about 20,000 deaths. Medical records are filled in by doctors, nurses / midwives and medical record personnel. However, in filling out medical records, incompleteness is often found and causes inaccurate information. The research design used a retrospective analysis approach. The variables in this study are incompleteness; authentication and documentation on the patient discharge summary form. The population in this study were inpatient medical records for Dengue Hemorrhagic Fever cases at the Hospital "X" Padang City from January to December 2019 as many as 45 medical record documents (discharge summary form) for inpatients. The results showed that there was the most incomplete data in the item code ICD 10 53% followed by 57% patient address